2015
DOI: 10.1021/acs.energyfuels.5b00853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical and Physical Treatments on the Properties of a Dolomite Used in Ca Looping

Abstract: Four diverse microstructured MgO-stabilized CaO sorbents with varying mixing characteristics of Ca and Mg were obtained from untreated, hydrated, precipitated, and milled dolomite. Different morphological characterizations (thermal decomposition, phase composition, morphology, and nitrogen adsorption) were performed, followed by an analysis of 30 carbonation/calcination cycles in a fixed-bed reactor. The mixed metal oxide (CaO−MgO) in the fresh calcined dolomite transformed into separate crystals of CaO and Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The presence of CaFe 2 O 4 and CaSiO 3 will affect the durability of the sorbents due to their low resistance to sintering. In contrast, MgO, with a sintering temperature of 1289 °C , , can effectively mitigate the rapid deactivation of the steel‐slag‐derived sorbents.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of CaFe 2 O 4 and CaSiO 3 will affect the durability of the sorbents due to their low resistance to sintering. In contrast, MgO, with a sintering temperature of 1289 °C , , can effectively mitigate the rapid deactivation of the steel‐slag‐derived sorbents.…”
Section: Resultsmentioning
confidence: 99%
“…35 A number of studies have attempted to employ treated/synthetic dolomite-based materials. Thus,Wang et al 36 and Sánchez-Jiménez et al 37 reported that dry ball-milling slightly enhanced the cyclic conversion of dolomite-derived sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of chemical elements such as Mg, Al and Si, during the carbonation-calcination cycles influences the skeleton/microstructure of the calcined sorbent, which hinders aggregation or sintering of CaO crystallites and helps in preserving the nanocrystalline CaO structure [46]. Some approaches have been carried out to improve the CO 2 capture by dolomitic carbonates, such as acid acetic pre-treatment [47] and two-step calcination under N 2 and CO 2 atmosphere to modify the sorbent microstructure [48], and ball milling of dolomite [49], even with water [50] or with ice and water to regenerate the dolomite and increase the CO 2 carrying capacity through the elimination of CaO and MgO segregation after cyclic carbonation-calcination cycles [51]. However, more detailed studies are still necessary to understand the role of MgO on the enhancement of the stability and multicycle carrying capacity performance observed for this alternative natural CaO-based sorbent, especially under a realistic industrial calcination gas atmosphere with a high concentration of CO 2 .…”
Section: Introductionmentioning
confidence: 99%